Influence of mass media on emergence of eating disorders amongst young people - Kaźmierczak, Natalia; Patryn, Rafał; Niedzielski, Antoni (Polish Journal of Public Health, 2013)
Introduction. Anorexia is an eating disorder, which is becoming more common among young people (especially women). This problem was explored at the medical level and cultural and personal causes of denying food were analyzed.Aim. The main aim of this article is to answer the question of whether the differences in self-perception are influenced by mass media and to what extent self-perception is influenced by cultural factors.Material and methods. The research was conducted in 2011 in the form of an on-line author-made questionnaire on a group of 100 respondents. The questionnaires were later put under analysis.Results. The examined group exhibited characteristic risk factors for anorexia. Seventy sic percent of the respondents believe that external appearance decides about life successes and for them, their look is a very important value. Majority of the respondents is significantly discontent with the look and shape of their body, as almost all believe that they should lose weight. Conclusions. Appearance constitutes essential value for the respondents. They aim at achieving ‘ideal beauty’ created by the mass media, regardless of health consequences. The image of ones’ own body is determined by information received from peers and through comparison with models promoted by the media